Simulation of the Gap Resonance Between Two Rectangular Barges in Regular Waves by a Free Surface Viscous Flow Solver. - Elie, B.; Reliquet, Gabriel; Guillerm, Pierre Emmanuel; Olivia, Thilleul; Ferrant, Pierre; Gentaz, L.; Ledoux, Alain (HAL CCSD, 2013)
International audience